A solution of the quasilinear elliptic equations by finite-difference method - Sapagovas, M. P. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:М. П. Сапаговас. Решение квазилинейных эллиптических уравнений методом конечных разностейM. P. Sapagovas. Kvazitiesinių eliptinio tipo diferencialinių lygčių sprendimas baigtinių skirtumų metodu